The Neutrophil-to-Lymphocyte Ratio is Associated with the Requirement and the Duration of Invasive Mechanical Ventilation in Acute Respiratory Distress Syndrome Patients: A Retrospective Study - Lijuan Yang; Chang Gao; Ying He; Xiaowan Wang; Ling Yang; Shiqi Guo; Jiahao Chen; Siyu He; Yuanxiao Sun; Ye Gao; Qiang Guo (Canadian Respiratory Journal)
Background. Acute respiratory distress syndrome (ARDS) is associated with high in-hospital mortality and most ARDS patients require ventilatory support. Applying appropriate ventilation strategies based on patients’ individual situations has a direct impact upon patients’ outcome. The neutrophil-to-lymphocyte ratio (NLR) has been shown to predict the early requirement of invasive mechanical ventilation (IMV) in patients with coronavirus disease 2019 (COVID-19). Our study aimed to investigate the relationship between baseline NLR and IMV in ARDS. Methods. A retrospective study was performed on patients who were diagnosed with ARDS using the Berlin definition and admitted to the First Affiliated Hospital of Soochow University from 2017 to 2022. Clinical data within 24 h after the ARDS diagnosis were collected from the medical record system. Based on the ventilation strategies during hospitalization, patients were divided into three groups and their clinical characteristics were compared. Furthermore, logistic regression analysis was used to screen the independent risk factors for IMV. STROBE checklist was used for this manuscript. Results. 520 ARDS patients were included and the median NLR value in IMV group was significantly higher than that of other groups (P<0.001). NLR was significantly associated with the requirement of IMV in ARDS patients (OR, 1.042; 95% CI, 1.025–1.060; P<0.001), other independent risk factors included PaO2/FiO2, Hb, lactate, and use of vasoactive drugs (all P<0.05). Moreover, we found that the duration of IMV was longer in patients with high NLR (8[IQR, 3–13], 10[IQR, 6–16], respectively, P=0.025). Conclusions. Our results revealed that high baseline NLR level was significantly correlated with an increased risk of IMV in patients with ARDS. Furthermore, higher NLR was associated with prolonged duration of IMV in patients with ARDS.